Oral atogepant mitigates spreading depolarization-induced pain and anxiety behavior in mice - Melih Z. Kaya; Pradeep Banerjee; Cenk Ayata; Andrea M. Harriott (The Journal of Headache and Pain)
Abstract Background Spreading depolarization (SD) is the most likely cause of migraine aura and may be linked to trigeminal nociception. Using minimally invasive optogenetic SD induction (opto-SD), we previously showed that SD triggers acute periorbital mechanical allodynia-like behavior, supporting SD-induced activation of migraine-relevant trigeminal pain pathways. Here, we tested whether selective oral calcitonin gene-related peptide (CGRP) receptor antagonist, atogepant, could ameliorate SD‐evoked pain and anxiety phenotypes. Methods Thirty‐two adult male and female Thy1‐ChR2‐EYFP transgenic mice (3–5 months, 18–30 g) housed in 12/12‐hr light/dark cycles were used. Under brief isoflurane anesthesia, a thin glass panel was placed on intact skull one week before the experiment to achieve translucency. A single SD was evoked using 10 s, 10 mW blue light stimulation over the motor cortex. One hour before SD or sham stimulation, atogepant (ato; 30 mg/kg in 100% PEG400) or vehicle (veh; 100% PEG400) was administered by oral gavage (4 mL/kg). Mechanical periorbital thresholds were measured 1 h after SD using von Frey monofilaments. Mouse grimace was then quantified using PainFace, an open convolutional neural network platform. Lastly, anxiety‐like behavior was examined in an open field. Groups were randomly assigned and the investigator blinded to group allocation (n = 8/group, balanced by sex), p < 0.05 was considered significant. Results There was a significant main effect of SD (p < 0.001) and atogepant (p = 0.015) on the periorbital threshold with an interaction (p < 0.001). A single opto-SD lowered periorbital threshold compared with sham (veh sham vs. veh SD: p < 0.001). SD also increased the total grimace score compared with sham (veh sham vs. veh SD: p = 0.014). Oral atogepant (30 mg/kg) alleviated SD-induced periorbital allodynia-like behavior (veh SD vs. ato SD: p < 0.001) but did not completely reverse SD-induced periorbital allodynia-like behavior (ato sham vs. ato SD: p < 0.001). Atogepant abolished the SD-induced facial grimace (ato sham vs. ato SD: p = 0.238). SD increased thigmotaxis score compared with sham (veh sham vs. veh SD: p = 0.016). Following atogepant treatment, there was no difference in thigmotaxis score in SD versus sham groups (ato sham vs. ato SD: p = 0.200). Conclusions These data suggest SD provokes a reproducible and robust facial pain phenotype in mice that is alleviated by pre-administration with atogepant. There was also improvement in SD-induced anxiety-like behavior following atogepant.